2014
DOI: 10.3201/eid2006.140402
|View full text |Cite
|
Sign up to set email alerts
|

Human Infection with MERS Coronavirus after Exposure to Infected Camels, Saudi Arabia, 2013

Abstract: We investigated a case of human infection with Middle East respiratory syndrome coronavirus (MERS-CoV) after exposure to infected camels. Analysis of the whole human-derived virus and 15% of the camel-derived virus sequence yielded nucleotide polymorphism signatures suggestive of cross-species transmission. Camels may act as a direct source of human MERS-CoV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
338
4
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(363 citation statements)
references
References 15 publications
15
338
4
6
Order By: Relevance
“…Evidence of infection in camels precedes the first evidence of human infection [6,7]. Recently, viral RNA has been detected in different specimens from camels and the virus has been isolated from nasal and faecal samples [6,[8][9][10][11][12].…”
Section: Zoonotic Transmissionmentioning
confidence: 99%
“…Evidence of infection in camels precedes the first evidence of human infection [6,7]. Recently, viral RNA has been detected in different specimens from camels and the virus has been isolated from nasal and faecal samples [6,[8][9][10][11][12].…”
Section: Zoonotic Transmissionmentioning
confidence: 99%
“…In a previous summary of 161 cases, 49 (30.4%) had contact with animals, 7 (4.3%) had contact with camels and another 7 (4.3%) had contact with sheep [29]. Recent reports showed that a patient was in contact with a diseased camel [56], and one patient treated a sick camel and that two MERS-CoV from the patient and the camel were identical [53,54].…”
Section: An Update On Mersmentioning
confidence: 99%
“…MERS-CoV was also isolated from camels by PCR in few instances [44,53,54]. Experimental infection of three camels with human isolates of MERSCoV was recently published [55].…”
Section: An Update On Mersmentioning
confidence: 99%
“…Camels play major role in human life in Middle East countries for transportation as well as entertainment. It was hypothesized that dromedary camels act as intermediate host for MERS-CoV infection from bats to humans (Memish et al, 2014). MERS-CoV was also detected in camel milk .…”
Section: Transmission Through Intermediate Hostmentioning
confidence: 99%